Purchasing decisions Nike sports shoes in students SMKN 1 Painan viewed from country of origin, brand image and product design - Djohannes Saputra Djohannes (Universitas Negeri Padang, 2022)
This study aims to determine the effect of country of origin, brand image and product design on purchasing decisions of Nike brand sports shoes for students of Smkn 1 Painan. The type of research used in this research is quantitative with a descriptive approach. Respondents in this study were 91 people with a total sampling technique. Analysis of the data used is multiple linear regression analysis. Partial test results show that there is a positive and significant influence of country of origin on purchasing decisions, there is a positive and significant influence of brand image on purchasing decisions, and there is a positive and significant influence of product design on purchasing decisions.